The Profitability, Capital Intensity, and Leverage, Their Effect on Tax Avoidance - Ammara Fayyaz Prasetyo; Retno Indah Hernawati; Harun Harun (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Tax avoidance is an effort made by companies to reduce the amount of tax payable. The main source of state revenue is taxes, but tax avoidance that exploits legal loopholes to reduce the tax burden remains an issue on the Indonesia Stock Exchange during the period 2020 to 2024. This study aims to examine the effect of profitability, capital intensity, and leverage on tax avoidance. This study applies a quantitative research approach using secondary data obtained from annual financial reports published on the official website www.idx.co.id as well as from the respective company websites. The analytical method employed is multiple linear regression. The research population consists of property and real estate companies listed on the Indonesia Stock Exchange from 2020 to 2024, with a final sample of 92 observations selected through purposive sampling. The findings reveal that profitability and capital intensity significantly influence tax avoidance, whereas leverage shows no significant effect on tax avoidance.